Survey of Caregivers’ Care Burden Perception Relating to Excretion-Related Actions of Parkinson’s Disease Patients (International Journal of Physiotherapy, 2022)
Background: Parkinson's disease (PD) is a progressive disease, and competence in performing activities of daily living declines during its progression, increasing caregiver’s care burden perception. Care in relation to excretion-related actions is frequently required against the background of motor and non-motor symptoms, and the contents of nursing care vary, including movement and dressing. Therefore, in this study, the care burden perception in relation to excretion related actions was investigated and classified by severity and intra-day changes in symptoms.Methods: The analysis included 25 caregivers of patients who had joined the Gunma Prefecture Branch of the Japan Parkinson’s Disease Association. The questionnaire items addressed care burden perceptions relating to nine excretion related actions. Responses were classified by whether the caregiver's movement was easy (ON) or difficult (OFF). The analysis involved placing the subjects in three groups (1/2, 3, and 4) based on the Hoehn and Yahr severity scale.Results: An increase in care burden perception due to the progression of symptoms was confirmed. In addition, although the difference between ON and OFF was not significant, care burden perception tended to be higher with OFF.Conclusions: Care burden perception increased with PD symptom progression, suggesting a tendency towardmore significant effects of intra-day symptom variation. This may constitute helpful information when considering rehabilitation linked to reducing caregiver’s care burden perception in connection with PD and/or reorganization/refitting of the domestic environment.Registration No. Ethical Review Board, Takasaki University of Health and Welfare (approval no. 2952).